Polydopamine-enabled distribution of polysiloxane domains in polyamide thin-film nanocomposite membranes for organic solvent nanofiltration - Liu, Jian; Mu, W.; Wang, J.; Liu, H.; Qin, Y.; He, J.; Guo, F.; Li, Y.; Li, Y.; Cao, X.; Zhang, P.; Lu, E. (Pergamon Press, 2018)
© 2018 Elsevier B.V. Thin-film nanocomposite (TFN) membranes have attracted growing interests for improving the energy efficiency of many chemical separation processes, while well-designed microstructures are essential to acquire high permeation flux, high selectivity and high stability for different types of permeates. Herein, a novel strategy to regulate the microstructures and solvent permeation properties of TFN membranes is developed. Hydrophobic polysiloxane domains are proposed to be evenly distributed within hydrophilic polyamide matrix with the mediation of polydopamine nanoparticles (PDNPs). To be specific, PDNPs treated by 3-(triethoxysilyl)- propylamine (APTES) allow PDMS converge on its surface, so as to form nano-sized poly(dimethylsiloxane) (PDMS) domains within the active layer of TFN membranes. With polyethyleneimine (PEI) as the aqueous phase monomer during conventional interfacial polymerization (IP), trimesoyl chloride not only acts as the oil phase monomer, but also reacts with the terminal hydroxyl groups of PDMS, facilitating the uniform dispersion of the nanoparticles within the PEI matrix. By tuning the ratio of PDNPs to PDMS, PDMS could be uniformly dispersed within the active layer together with PDNPs, which effectively construct hydrophobic pathways for nonpolar solvents. A maximum permeate flux for n-heptane of 7.9 L m-2h-1bar-1at 10 bar is achieved, along with moderate area swelling (3.16%) and rather low MWCOs (below 400). Meanwhile, these TFN membranes containing PDMS domains still display appropriate permeate fluxes for polar solvents due to the maintenance of hydrophilic pathways, as well as enhanced rejection ability and potential long-term operation stability than the control membranes.